The last coyote - Connelly, Michael (New York : St. Martin's Paperbacks, 1996)
Los Angeles police detective Harry Bosch is placed on forced leave for hitting his boss. He decides to take advantage of his free time to solve a case which has obsessed him all his life: the murder of a prostitute, his mother.
National College of Business and Arts
Keywords: Murder -- Investigation -- Fiction; Detective and mystery fiction